2011
DOI: 10.1111/j.1399-3046.2011.01584.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor cell‐derived acute myeloid leukemia after second allogenic cord blood transplantation in a patient with Fanconi anemia

Abstract: DCL following hematopoietic stem cell transplantation has been reported in approximately 5% of all leukemic relapses. There have been several reports on DCL, mainly AML after umbilical cord blood transplantation. In this case study, we present a young boy diagnosed with Fanconi anemia who underwent an umbilical cord blood transplantation. Because of the graft failure, he was retransplanted one month later, also with a cord blood transplant. Two years after the second transplant, he developed AML, where 100% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…As 5-azadC is a more modern and targeted treatment option, it may be suggested as an alternative treatment to these patients. In one reported case, a Fanconi’s anemia patient with an AML derived from healthy donor cells received complete remission after a 5-azaC treatment (42). Although we do not discourage, we would recommend cautious use of 5-azadC in treatment of AML in Fanconi’s anemia patients, as we show that cells defective in the Fanconi’s anemia pathway are hypersensitive to 5-azadC.…”
Section: Discussionmentioning
confidence: 99%
“…As 5-azadC is a more modern and targeted treatment option, it may be suggested as an alternative treatment to these patients. In one reported case, a Fanconi’s anemia patient with an AML derived from healthy donor cells received complete remission after a 5-azaC treatment (42). Although we do not discourage, we would recommend cautious use of 5-azadC in treatment of AML in Fanconi’s anemia patients, as we show that cells defective in the Fanconi’s anemia pathway are hypersensitive to 5-azadC.…”
Section: Discussionmentioning
confidence: 99%
“…Donor‐derived myelodysplastic syndrome and acute leukaemia (DD‐MDS/AL) are rare adverse events after allogeneic haematopoietic stem cell (HSC) transplantation. Originally identified in 1971 (Fialkow et al , ), nearly 90 cases have now been reported in the literature (Hertenstein et al , ; Ruiz‐Argüelles et al , ; Wang et al , ; Wiseman, ; Fraser et al , ; Matsunaga et al , ; Sevilla et al , ; Yamazaki et al , ; Gustafsson et al , ; Rodriquez‐Macias et al , ; Nakamizo et al , ). Based on several reviews, the incidence of DD‐MDS/AL has been estimated to be between 0·12% and 5% (Hertenstein et al , ; Ruiz‐Argüelles et al , ; Wang et al , ; Wiseman, ).…”
mentioning
confidence: 99%
“…Since the first documented cases in 2005, reports of DD‐MDS/DD‐AL after umbilical cord blood (UCB) transplantation have been more frequent than with other HSC sources (Fraser et al , ; Matsunaga et al , ; Sevilla et al , ; Yamazaki et al , ; Gustafsson et al , ; Rodriquez‐Macias et al , ; Nakamizo et al , ), causing some investigators to speculate that the incidence of DD‐MDS/AL may be higher after UCB relative to bone marrow or mobilized peripheral blood transplantation (Greaves, ; Greaves et al , ). Greaves et al () raised the important concern that UCB might carry an increased risk of DD‐MDS/AL due to the presence of these pre‐leukaemic clones previously shown to exist in a proportion of UCB samples (Greaves, ; Greaves et al , ).…”
mentioning
confidence: 99%
“…Reported cases with DCL, mainly acute myeloid leukemia after umbilical cord blood transplantation, are increasing according to the recent advance of diagnostic procedures such as short tandem repeat (STR) testing (4)(5)(6)(7). Although multiple mechanisms for developing DCL have been proposed, considering the diversified phenotypes of DCL with varied latency periods in previously reported cases, the pathogenesis of DCL could involve more than a single pathway (1,3,7).…”
Section: Introductionmentioning
confidence: 99%